2012
DOI: 10.1186/1471-2296-13-112
|View full text |Cite
|
Sign up to set email alerts
|

Is the Scale for Measuring Motivational Interviewing Skills a valid and reliable instrument for measuring the primary care professionals motivational skills?: EVEM study protocol

Abstract: BackgroundLifestyle is one of the main determinants of people’s health. It is essential to find the most effective prevention strategies to be used to encourage behavioral changes in their patients. Many theories are available that explain change or adherence to specific health behaviors in subjects. In this sense the named Motivational Interviewing has increasingly gained relevance. Few well-validated instruments are available for measuring doctors’ communication skills, and more specifically the Motivational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Interpretivism, focused on understanding the meaning of the research topic from the perspective of the participants, was the overarching epistemology given in most of the 19 articles that described some methodological principle in relation to Delphi. Reference was simply made to a qualitative research approach in six of the studies (Chan, Wey, & Chang, 2014 ; Daim, Laakso, Rubin, & Linturi, 2012 ; McNichols, 2010 ; Pérula et al, 2012 ; Santos & Gomes, 2010 ; Traynor, Boyle, & Janke, 2013 ; Van Kemenade, Hardjono, & De Vries, 2011 ), which is generally consistent with interpretivist epistemology and constructivist ontology (Andrews, Sullivan, & Minichello, 2004 ). A qualitative approach to achieve quasi-objective quantitative estimates was discussed in four studies (Brody, Byham-Gray, Touger-Decker, Passannante, & Maillet, 2012 ; López-Sánchez & Pulido-Fernández, 2014 ; Palo & Tähtinen, 2011 ; Tang & Wu, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interpretivism, focused on understanding the meaning of the research topic from the perspective of the participants, was the overarching epistemology given in most of the 19 articles that described some methodological principle in relation to Delphi. Reference was simply made to a qualitative research approach in six of the studies (Chan, Wey, & Chang, 2014 ; Daim, Laakso, Rubin, & Linturi, 2012 ; McNichols, 2010 ; Pérula et al, 2012 ; Santos & Gomes, 2010 ; Traynor, Boyle, & Janke, 2013 ; Van Kemenade, Hardjono, & De Vries, 2011 ), which is generally consistent with interpretivist epistemology and constructivist ontology (Andrews, Sullivan, & Minichello, 2004 ). A qualitative approach to achieve quasi-objective quantitative estimates was discussed in four studies (Brody, Byham-Gray, Touger-Decker, Passannante, & Maillet, 2012 ; López-Sánchez & Pulido-Fernández, 2014 ; Palo & Tähtinen, 2011 ; Tang & Wu, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Internal validity was achieved by implementing comprehensive control measures during the study, from the selection of the study design (randomization in groups), to the use of an educational program for physicians based on the eight MI skills. In addition, we assessed participants' adherence to the intervention protocol and verified its reliability; implementation differences between the two arms of the study were assessed using a measure tool previously validated (EVEM) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a quality control measure and to assess physicians' adherence to the protocol, we recorded four real interviews between each participating physician and one of the patients recruited. All video recordings were scored using a Motivational Interviewing Assessment Scale (EVEM) [ 18 ]. Our research group previously demonstrated EVEM's reliability in assessing psychometric properties (intraclass correlation coefficient: >0.96; Cronbach's alpha: >0.95); as well as its validity and sensitivity to change.…”
Section: Methodsmentioning
confidence: 99%
“…[4] We have detailed in Box 1, the processes and measurements that were tested with each version of the scale. Differences in sample sizes between the original protocol and the validation process were due to feasibility criteria and losses in the development of the Dislip-EM study.…”
Section: Methodsmentioning
confidence: 99%
“…In Spain, where the development of the Measuring Motivational Interviewing Skills Scale (MIAS in English; 'Escala para la Valoraci on de la Entrevista Motivacional', EVEM scale, in Spanish) was completed, [4] practitioners are not usually able to spend more than 10 min in consultations with their patients. [5] The MITI advises 20-min samples of encounters when using scale per the author's methodology.…”
Section: Introductionmentioning
confidence: 99%